Pemberdayaan Masyarakat Pesantren Husnul Khotimah berbasis Teknologi dengan Implementasi Pembangkit Listrik Tenaga Terbarukan - Budi Prasetya; Yuyun Siti Rohmah; Kris Sujatmoko; Dharu Arseno; Sugondo Hadiyoso (Politeknik Piksi Ganesha Indonesia, 2025)
Husnul Khotimah Islamic Boarding School faces challenges in meeting the need for electricity supply due to 24-hour operations. This causes high operational costs, especially for electricity. Until now, there have been no efforts to implement alternative energy sources due to limited knowledge and budget. This research in the form of community service proposes empowering the Islamic boarding school community through renewable energy-based power generation technology, namely solar and wind power. This implementation aims to reduce dependence on conventional electricity, reduce operational costs, and increase the understanding of the Islamic boarding school community regarding green energy technology, namely solar and wind energy. The methods used include feasibility studies, planning, installation, and training the Islamic boarding school community. The expected results are the creation of an efficient and sustainable renewable energy system, as well as increasing the capacity of the Islamic boarding school community in managing independent energy resources. This empowerment is expected to be a model that can be replicated by other Islamic boarding schools in overcoming similar problems.